Peningkatan Kapasitas Literasi Melalui Budaya Baca dan Pengembangan Karakter di Dusun Coci Desa Banua Adolang Kecamatan Pamboang Kabupaten Majene Provinsi Sulawesi Barat - Saputra, Aco Nata; Aziz R., Muhammad Tanzil; Novitasari, Ika; Amiruddin, Ahmad (CV. Literasi Indonesia, 2022)
A person's literacy level can be assessed through personal characteristics which are horizontally very closely related. A person's insight, mentality, and behavior are strongly influenced by interests and tendencies in reading books. Since 75 years of Indonesia's independence, the literacy rate in Indonesia is still in the low category. This is strongly influenced by various factors, one of which is the availability of reading materials and literacy facilities. This problem should not be allowed to drag on, it needs serious attention from the government, academics, and education leaders. The discourse on improving reading culture has become a central issue in developing the human resource capacity to produce Indonesian people with character. The development of Indonesian human character is highly dependent on reading culture. The attachment between reading culture and the development of Indonesian human character is expected to have implications for the quality of advanced and modern Indonesian people.